MEANS OF PERSONAL PERSONALITY IN UZBEK LANGUAGE TEXTS - Sayyora Qurbonova; Rafiqova Malika Faxriddinovna (Galaxy International Interdisciplinary Research Journal, 2022)
This scientific article provides detailed comments on the means of expression in the Uzbek language in the description of personality.